Differences in the Presentation and Progression of Parkinson's Disease by Sex. Issue 1 (1st October 2020) - Iwaki, Hirotaka; Blauwendraat, Cornelis; Leonard, Hampton L.; Makarious, Mary B.; Kim, Jonggeol J.; Liu, Ganqiang; Maple‐Grødem, Jodi; Corvol, Jean‐Christophe; Pihlstrøm, Lasse; van Nimwegen, Marlies; Smolensky, Luba; Amondikar, Ninad; et al.
ABSTRACT: Background: Previous studies reported various symptoms of Parkinson's disease (PD) associated with sex. Some were conflicting or confirmed in only one study. Objectives: We examined sex associations to PD phenotypes cross‐sectionally and longitudinally in large‐scale data. Methods: We tested 40 clinical phenotypes, using longitudinal, clinic‐based patient cohorts, consisting of 5946 patients, with a median follow‐up of 3.1 years. For continuous outcomes, we used linear regressions at baseline to test sex‐associated differences in presentation, and linear mixed‐effects models to test sex‐associated differences in progression. For binomial outcomes, we used logistic regression models at baseline and Cox regression models for survival analyses. We adjusted for age, disease duration, and medication use. In the secondary analyses, data from 17 719 PD patients and 7588 non‐PD participants from an online‐only, self‐assessment PD cohort were cross‐sectionally evaluated to determine whether the sex‐associated differences identified in the primary analyses were consistent and unique to PD. Results: Female PD patients had a higher risk of developing dyskinesia early during the follow‐up period, with a slower progression in activities of daily living difficulties, and a lower risk of developing cognitive impairments compared with male patients. The findings in the longitudinal, clinic‐based cohorts were mostly consistent with the results of the online‐only cohort. Conclusions: We observed sex‐associated contributions to PD heterogeneity. These results highlight the necessity of future research to determine the underlying mechanisms and importance of personalized clinical management. © 2020 International Parkinson and Movement Disorder Society